Effects of varying eye temperature on flight performance during visual stimulation of dicronorrhina derbyana species - Quek, Zhao Lun (2017)
Insects and their relationship to ambient temperature have long been documented and researched upon. Due to their cold-blooded characteristics, the behavioural pattern of insects in their flight, mating behaviour and sustenance are deeply influenced by the temperature of the environment around them. It has been recently observed that the Dicronorrhina derbyana beetle has an elevated temperature of its eyes during its flight relative to the rest of its body. This study examines the impact of the eye temperature of the Dicronorrhina derbyana beetle on its performance in flight when subjected to various visual stimuli. The study involves the collection of the Dicronorrhina derbyana beetle’s flight data in response to a predefined visual stimulation sequence while varying the eye temperature by means of cooling. The beetle is subjected to different visual stimulus by the means of an LED panel to evoke the various phases of flight while artificial cooling is carried out on the head of beetle. The aerodynamic force is measured simultaneously via a Force Sensor along with the beetle’s wing-beat frequency with a microphone during the experiment. The preliminary statistical analysis from the processed data after the experiment shows strong evidence that the eye temperature impacts the beetle’s flight behaviour directly.